Concert and contest collection for Eb or BBb bass (tuba-sousaphone) with piano accompaniment - VOXMAN, H. (Rubank Inc., 1922)
Andagio and allegro from sonat No. 7 ..G.F. HandelnAir gai.....G.P.BerlioznAndante and Allegro...........Robert ClerissenFirst movement from concerto for horn...........W.A. MozartnLArgo and allegro..............B. MArcello